2013
DOI: 10.1097/wad.0b013e31824a7df4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Striatal Degeneration in Frontotemporal Dementia

Abstract: Behavioral variant frontotemporal dementia and semantic dementia have been associated with striatal degeneration, but few studies have delineated striatal subregion volumes in vivo or related them to clinical phenotype. We traced caudate, putamen, and nucleus accumbens on MR images to quantify volumes of these structures in behavioral variant frontotemporal dementia, semantic dementia, Alzheimer’s disease, and healthy controls (n = 12 per group). We further related these striatal volumes to clinical deficits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 55 publications
9
35
0
1
Order By: Relevance
“…These findings further corroborate the specificity of the VMPFC [5] and striatum [40,41] in bvFTD. VMPFC changes, in particular in orbitofrontal and anterior cingulate cortices in bvFTD [42,43], that have been associated with many of the classical behavioural features in the disease, notably disinhibition, apathy, loss of insight and reduced empathy [44][45][46].…”
Section: Sv-ppa Vs Bvftdsupporting
confidence: 76%
“…These findings further corroborate the specificity of the VMPFC [5] and striatum [40,41] in bvFTD. VMPFC changes, in particular in orbitofrontal and anterior cingulate cortices in bvFTD [42,43], that have been associated with many of the classical behavioural features in the disease, notably disinhibition, apathy, loss of insight and reduced empathy [44][45][46].…”
Section: Sv-ppa Vs Bvftdsupporting
confidence: 76%
“…This was further corroborated by structural neuroimaging studies that identified striatal atrophy in FTD, again with the most severe changes seen in bvFTD 78 79. In both bvFTD and PPA-nfv, atrophy has been shown in the caudate and putamen, as well as nucleus accumbens, with putaminal atrophy in bvFTD being more right lateralised and less severe than caudate atrophy 78 79.…”
Section: Disorders With Less Described Striatal Dysfunctionmentioning
confidence: 56%
“…By comparison, bvFTD patients have been reported to show a 25% caudate volume reduction compared with age-matched controls 91. Similarly, the nucleus accumbens and putamen appeared to be relatively spared in AD,78 80 although some studies have reported putaminal volume loss, in particular for the left putamen 92…”
Section: Disorders With Less Described Striatal Dysfunctionmentioning
confidence: 99%
“…While not yet described in FTD models, repetitive grooming has been described in several knockout mouse lines. 118120 Again, there are interesting neuroanatomic parallels, as the striatum seems to be highly involved in both FTD-associated repetitive behavior 121,122 and repetitive grooming in mutant mice. 119,120 …”
Section: Future Opportunities With Ftd Modelsmentioning
confidence: 99%